Diksi, Gaya Bahasa, Dan Citraan Lirik Lagu Para Pencari-Mu Karya Ungu (Kajian Stilistika) - Julianto, Indra Rasyid (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2023)
This research contains the language of the lyrics of the song Para Pencari-Mu popularized by the music group Ungu. The band Ungu has varied and interesting songs. The lyrics of the song Para Pencari-Mu popularized by the music group Ungu contain diction, language style, and imagery that are reviewed through stylistic studies. As one of the masterpieces of songs with a very famous religious theme, researchers focus on stylistic studies to find out the meaning in the lyrics of the song. Stylistics is a literary analysis that focuses on the meaning of language style on the characteristics of the author or creator of the work. In this case, the research aims to (1) describe the diction in the song lyrics; (2) explain the language style in the song lyrics; and (3) detail the imagery in the song lyrics. This article contains descriptive qualitative research. This research includes data collection techniques, namely reading and writing techniques sourced from song lyrics. The results of this study describe the diction of Para Pencari-Mu song lyrics in which there are denotative, connotative diction, typical greetings and proper names, and the meaning of foreign or absorbed words. The diction affects the broad meaning in the lyrics of Para Pencari-Mu. Then the meaning of the language style in the song lyrics is also found in metaphor and hyperbole. Then the imagery in the song lyrics is visual and movement imagery.